2004
DOI: 10.1381/096089204322857726
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Wall Necrosis from Organo-axial Volvulus as a Late Complication of Laparoscopic Gastric Banding

Abstract: We present a case of massive gastric wall necrosis associated with volvulus of the stomach occurring 17 months after laparoscopic gastric banding. The 19- year-old female was admitted to our hospital with acute abdominal pain with rapid deterioration from massive necrosis of a distended stomach which perforated distal to the gastric band, accompanied by splenic infarction. Total gastrectomy and spenectomy were required. We present this very rare complication which should be recognized and treated early, so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
1
11
0
1
Order By: Relevance
“…He had guarding and rebound tenderness. The leukocyte count was higher than 14,000/mm 3 . The plain abdominal X-ray in the lateral decubitus view showed presence of free air within the abdomen (Figure 1).…”
Section: Case Presentationmentioning
confidence: 77%
See 1 more Smart Citation
“…He had guarding and rebound tenderness. The leukocyte count was higher than 14,000/mm 3 . The plain abdominal X-ray in the lateral decubitus view showed presence of free air within the abdomen (Figure 1).…”
Section: Case Presentationmentioning
confidence: 77%
“…Failure to diagnose the condition or presentation of the patient to the hospital during the late period may cause necrosis and rupture that may lead to death (2). The pathogenesis is still controversial (3). The most frequent complaints are abdominal pain and vomiting, and are usually accompanied by abdominal bloating (4).…”
Section: Introductionmentioning
confidence: 99%
“…Erenbourg was described a ligament called 'gastro-pancreatic', and they suggested that the presence of this anatomic element can suggest new interpretations of the embryological development of the pancreas [3]. Several gastric volvulus cases have been reported after laparoscopic gastric banding, usually occurring after placement of the band [4][5][6]. They recommended not to dissect the posterior wall of the stomach during band replacement.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 1,000 LAGB patients, ten patients experienced band slippage, but only one patient required intervention for gastric necrosis [2,4]. Four other cases of gastric necrosis as a result of late slippage have been reported in the literature, three of which required partial or total gastrectomy [5][6][7][8]. All patients reported in the literature had acute symptoms of obstruction at the time of their presentation.…”
Section: Discussionmentioning
confidence: 99%